Zakat on Banknotes in Fiqh Syᾱfi’ῑyah Perspective - Muhammad Yasir; Tengku Sirajuddiin; Ahmad Alfajri (Budapest International Research and Critics University, 2019)
One of the Islamic Shari'a is zakat, in addition to the value of the charity of zakat, it also serves as an economic boost for the poor. The obligation of zakat can be understood implicitly from the Qur'an and Hadith but the methods and criteria of zakat are not fully explained, this is where the different assumptions that lead to different practices and criteria are established, one of which is banknotes where some say obligatory and some not . This research is focused on zakat on banknotes, and the reasons that require paper money zakat according to the study of syᾱfi'ῑyahi fiqh. To obtain accurate data in this study, the authors conducted a literature review by using qualitative research methods. The data collection techniques were carried out by library studies, namely selecting and analyzing relevant literature and were seen as supporting material that discussed the problem of zakat money. From the results of this study, the authors find that banknotes is said to be obligatory, some said it is not mandatory. Opinions that say must give a reason, if the current position of banknotes in lieu of dirhams and dinars in the past then the wisdom that exists in dirhams and dinars is also on paper money that is valid in the present and when viewed in terms of the value of paper money This is instead of the value of gold and silver, which means that banknotes owned by someone instead of gold and silver are only in the form of the paper money must be zakat. Opinions that say they are not obliged to give reasons do not come up arguments that require currencies other than dirhams and dinars to be zakati, the lessons in gold and silver are not in currencies other than gold and silver. And currencies other than gold and silver have nothing in common with dirhams and dinars which can be explained to the obligatory zakat.